#### Answer

$x=-1$

#### Work Step by Step

Simplify $\dfrac{2}{x+2}+\dfrac{4}{x-2}=\dfrac{x-1}{x^2-4}$
Thus, $\dfrac{2}{x+2}+\dfrac{4}{x-2}=\dfrac{x-1}{(x+2)(x-2)}$
or, $2(x-2)+4(x+2)=(x-1)(1)$
or, $2x-4+4x+8=x-1$
or,$5x =-5$
Hence, $x=-1$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$x=-1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.